Diagnostic accuracy of loop-mediated isothermal amplification for pulmonary tuberculosis in China - Lin, Jing-Jing; Xi, Xiu-Hong; Xia, Lu; Tan, Yao-Ju; Chen, Yu; Di, Hong-Qin; Chen, Zhen-Hua; Yu, Ting; Wei, Jian-Hao; Fang, Peng; Lin, Xiao-Ma; Su, Bi-Yi; et al. (Frontiers in Tropical Diseases, 2022)
Objectives To evaluate the diagnostic accuracy of Loop-Mediated Isothermal Amplification Platform (LAMP) in detecting pulmonary tuberculosis (PTB). Methods This multicenter prospective study was conducted at six sites in China from June, 2018 to December, 2019. Patients with suspected PTB were consecutively recruited and respiratory samples were collected from all patients. LAMP, Xpert MTB/RIF assay (Xpert), fluorescence smear microscopy, and BACTEC MGIT 960 liquid culture (Mtb culture) were performed for each sample. Diagnostic accuracy indices were calculated against Mtb culture results. Results A total of 845 participants were enrolled, but only 799 were included in the analysis. The sensitivities of LAMP, Xpert, and smear microscopy were 78.6% (239/304), 82.2% (250/304), and 63.8% (194/304), respectively, and their specificities were 88.7% (439/495), 86.1% (426/495), and 94.9% (470/495), respectively. The LAMP assay showed substantial agreement with other tests (kappa 0.64–0.79). Conclusion The LAMP assay performs as well as Xpert MTB/RIF assay and Mtb culture in tertiary-care hospitals. It can be used as an alternative test for detecting PTB with the advantages of being fast, inexpensive, and easy to operate.